Perancangan pet furniture dengan implementasi Teknik Makrame - Vanessa Joanna Prianto; Sriti Mayang Sari (Institut Seni Indonesia Yogyakarta, 2021)
There are many cases where humans and their pets, especially dogs do activities in their home. To provide the medium for both sides, some tools and furniture are needed for their activities. The purpose of this study is to design a furniture that supports human and dogs’ activities without losing its aesthetic values. Designing methods that being used in this study would be Design Thinking that consist of understand, define, ideate, prototype, and test. The designing process started with observation to determine the design boundary for pet’s furniture and find materials that suitable for dogs. This furniture design will use a concept called F.U.N (Functionality-Unity-New) with implementing macrame technique as its finishing touch. Facilities that this furniture give are humans seat, dog’s sleeping place, dog’s playground, dog’s eating and drinking places. Pet furniture design can be used indoors or outdoors depends on the user needs. The materials that being used are lightweighted so it is easy to move, coated with Technical Decorative Sheet (TDS) as its finishing, and macrame to give aesthetic values to the pet furniture.